A Comparison of the Wage Gap between the Public and Private Sectors in Indonesia (West Science Business and Management, 2025)
This study examines salary differences between the public and private sectors in Indonesia from the perspective of employees. Using a qualitative approach, interviews were conducted with 10 informants representing diverse industries and roles. Findings reveal significant contrasts between the sectors: public sector employees prioritize job security, stability, and comprehensive benefits, while private sector employees value higher salaries, performance-based rewards, and career growth opportunities. Despite these differences, both groups emphasize the importance of fairness and transparency in compensation systems. The study provides valuable insights for policymakers and employers to develop equitable and competitive remuneration strategies that address employees’ priorities and support organizational goals.